Association between water source and chronic gastrointestinal diseases in Chinese: A cross-sectional and longitudinal study - Zhang, Hehua; Xia, Yang; Chang, Qing; Zhang, Xiangsu; Zhao, Yuhong (Frontiers in Public Health, 2022)
Background: Gastrointestinal health is closely associated with the quality of the water supply. However, long-term associations between the water supply type and chronic gastrointestinal disease (CGD) are unclear. Method: The water supply was categorized as “tap-water” or “non-tap water” use. Changes in water source use were categorized into four types: “non-tap water both at baseline and in follow-ups,” “non-tap water at baseline and tap-water in follow-ups,” “tap-water at baseline and non-tap water in follow-ups,” or “tap-water at baseline and in follow-ups.” We explored the association between tap-water use (and changes therein) and the risk of CGD in a cross-sectional and longitudinal population study based on national cohort data from 2011–2018. Results: After the inclusion and exclusion process, 13332 and 9688 participants were included in the cross-sectional and longitudinal analyses, respectively. Tap-water use was associated with fewer CGD cases at baseline (OR = 0.98, 95% CI: 0.90, 1.07). Tap-water use at baseline was associated with significantly lower incidence of CGD in follow-ups (HR = 0.70, 95% CI: 0.70, 0.90). Compared with consistent non-tap water use in both baseline and follow-ups, switching from non-tap water to tap-water use in follow-ups was associated with a lower risk of CGD (HR = 0.79, 95% CI: 0.64, 0.97), tap water use at both baseline and in follow-ups was associated with a lower risk of CGD (HR = 0.72, 95% CI: 0.59, 0.88). The decreased risk of CGD followed a linear trend (P for trend < 0.01). Adjustment for indoor solid fuel use and outdoor air pollution exposure to PM2.5 did not change the association between tap water use and CGD. Conclusion: Tap water use was associated with a reduced risk of incident CGD. The benefit of tap water use was time dependent. The results from this study should aid in effect assessment for water purification strategies and public decision support for gastrointestinal health management.